Implementation of Constructivism Model to Improve Reading Ability to The Second Year Students of MAS Al Zahrah Bireuen - Ullya Zainura (English Education Journal, 2018)
The objectives of this research are to know how Constructivism Model can be implemented in Reading Comprehension, to know the students’ response toward the implementation of Constructivism Model in teaching reading ability and to identify whether the Constructivism Model can improve the students’ reading ability to the second year students of Mas Al Zahrah. The subject of this research was an English teacher who teaches at the second year students and students of XI/B in the 2016/2017 academic year. This is a kind of action research which employs qualitative method in nature. Two cycles were conducted in this research. Each of this cycle consisted of the activities namely planning the action, implementing the action, observing the action, and reflecting. The instruments used in data collection were observation, questionnaire, and test. The result showed that the implementation of Constructivism Model was successful in improving the students’ reading ability. The result of the test in cycle 1 was 66.85 and in cycle 2 was 84.25. It means that the Constructivism Model can be used to improve the students’ reading ability. In addition, the students gave positive response toward the implementation of this model in improving their reading comprehension. It can be concluded that the Constructivism Model can be used in the teaching reading and also give positive effect to the students in learning reading comprehension.